Studi Komparasi Antara Model Pembelajaran Discovery Learning dan Self Directed Learning terhadap Kemampuan Pemecahan Masalah Siswa - Zafri, Dicky Ezaldi; Rizki, Lussy Midani; Zulhendri, Zulhendri (Journal of Education Research, 2023)
This study aims to determine the differences between the Discovery Learning learning model and the Self Directed Learning method on the problem solving abilities of XI grade students at SMK Negeri one Kuok. This type of research is quantitative research, with the research model used is Quasi Experiment. The population in this study were all students of class XI SMK Negeri one Kuok with a total of ninety-nine students. The sampling technique used was a random sample technique. The research subjects were divided into two, namely class XI TPHP as a Discovery Learning class and class XI ATP as a Self Directed Learning class. Retrieval of research data using a posttest instrument that has been validated. The results showed that the TPHP this means that there are differences in mathematics learning outcomes between students of the Discovery Learning and Self-Directed Learning models on the Problem Solving Ability of Class XI Students at SMK Negeri satu Kuok.